Skeletal muscle hypertrophy: molecular and applied aspects of exercise physiology - Arantes, V. H. F.; Paulucio da Silva, D.; Luiz de Alvarenga, R.; Terra, A.; Koch, A.; Machado, M.; Saboia Pompeu, F. A. M. (German Journal of Exercise and Sport Research, 2020)
Studies from the 20th century had proposed that exercise-derived anabolism is the result of acute release of anabolic hormones. Recent advances in molecular biology have validated the hormonal theory, but have raised the question of whether exercise-induced anabolic hormones are related to chronic hypertrophy. Intrinsic factors of muscle contraction, on the other hand, seem to play an important role in exercise-induced protein synthesis and hypertrophy. This review seeks to highlight the role of anabolic pathways related to resistance exercise and express its applicability in resistance training considering the following variables: (a) intensity; (b) volume; (c) rest interval; (d) types of contraction; (e) velocity of contraction; (f) exercise order; and (g) frequency. We conclude that resistance training-induced hypertrophy is likely explained by intrinsic factors rather than by the hormonal theory. Regarding the following training recommendations, multiple sets, long rest intervals, dynamic and high-velocity contractions and prioritizing the exercise order are most likely to produce the greatest enhancement in skeletal muscle hypertrophy. Training intensity may vary, as low (30% one-repetition maximum [1RM]) or high (80% 1RM) intensities induce similar improvements in hypertrophy when performed to a maximal level of effort. Likewise, training frequency may vary according to individual needs, as the total volume performed within a training week appears to be more strongly related to hypertrophy than the number of weekly training sessions. This review contributes to the development of sports performance, aesthetics, and quality of life, and to the prevention or treatment of muscle loss caused by aging or illness.